Characterization and utilization of nodular sepiolite (meerschaum) from Eskisehir (Turkey) - Isik, Iskender; Uz, Veli; Austin, George S.; Isik, C. Eren (Elsevier Science Bv, 2010)
In this study, the characterization of nodular sepiolites (right and sandy meerschaum) from Eskisehir (Turkey) Province was studied in order to determine the cause of cracking in sandy meerschaum products. Significant differences between the two types of meerschaum were only observable with SEM and BET analyses. Thus, it was concluded that the microstructure of sandy meerschaum was the main factor for its cracking. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Sepiolite; Eskisehir; Meerschaum articles